2008
DOI: 10.1111/j.1743-6109.2008.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Psychological Status among Males and Females with Ischemic Heart Disease

Abstract: Introduction Patients with coronary artery disease (CAD) may also suffer from mental and sexual problems, and we should consider the mutual influence such conditions have on each other. However, the interrelation between sexual and mental problems in the context of CAD has not been fully investigated, especially when it comes to gender. Aim Our aim was to evaluate sexuality and psychiatric symptoms among patients with CAD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…The rates of SD increased to 34.8%, 21.5% and 20.1%, respectively, 12 weeks after MI. Finally, in 2007, Kazemi et al (28) examined sexual activity and psychiatric symptoms among patients with CAD and the relationships between these variables for each gender in 550 married patients with CAD (397 men and 153 females; average age = 57 years). The data revealed that 45.8% of women with CAD showed anxiety symptoms and that 20.3% suffered from depression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rates of SD increased to 34.8%, 21.5% and 20.1%, respectively, 12 weeks after MI. Finally, in 2007, Kazemi et al (28) examined sexual activity and psychiatric symptoms among patients with CAD and the relationships between these variables for each gender in 550 married patients with CAD (397 men and 153 females; average age = 57 years). The data revealed that 45.8% of women with CAD showed anxiety symptoms and that 20.3% suffered from depression.…”
Section: Resultsmentioning
confidence: 99%
“…In women, this process occurs during menopause and can cause various sexual problems (21). Depression is an important risk factor for SD, as this condition may compromise sexual desire, and unsatisfying sexual performance is related to depression (20,23,24,28). In the absence of sexual desire, sexual fantasies are rare or fleeting sexual stimuli and may not occur efficiently, preventing completion of the sexual response cycle (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that symptoms of anxiety and depression are more severe in women with CAD compared with men (9)(10) . The results, however, are inconclusive.…”
Section: Anxiety and Depression Among Men And Women Who Underwent Permentioning
confidence: 99%
“…The annual mortality rate due to ischemic heart disease is currently 5% among males and 3.65% among females [4]. Several studies have identified gender differences in CAD susceptibility that likely account for the higher mortality rate among males [5, 6]. …”
Section: Introductionmentioning
confidence: 99%